Penalaran moral pada siswa SLTP umum dan Madrasah Tsanawiyah - Zidni Immawan Muslimin (Universitas Ahmad Dahlan, 2004)
The purpose of this study is to find out the differences of moral reasoning between students of Sekolah Lanjutan Tingkat Pertama Negeri (SLTPN) and students of Madrasah Tsanawiyah Negeri (MTs N).The total subjects of the research were 53 students. The students of SLTPN